(untitled) (Journal of Parents and Teachers, 2014)
The field of special educational needs is becoming increasingly broad and therefore more support and assistance instruments are required. The field of computer development is progressively being adapted to the interests of educators and support staff for pupils with special educational needs. Some useful examples within this field are different technical aids such as specific technological devices and instruments, as well as Internet services where we can collect ideas and forms of assistance. In the following article an attempt has been made to reflect on existing technological resources in the field of educational technologies in view of the diversity of profiles that can be found in the school integration of pupils with SEN. It provides an overview of the different technological resources useful in the care of motor disabilities and giftedness.